Manajemen Strategik Pengawasan Isi Siaran Televisi Swastasiaran Jaringandi Balioleh Komisi Penyiaran Indonesia Daerah Bali - Emma Ratna Sari Moedy (Jurnal Ilmiah Cakrawarti, 2019)
As one of the electronic media, television is present in the most private space of television toactually live from advertisers. The public or the public in this case is placed in one position as acommodity that is able to capture advertisers who can provide income for the life of the televisionstation. human life. Television is present in the family room, even the bedroom. audiences have the rightto receive quality shows that are useful for them, and not only give priority to the benefits of televisionstation owners. The media has so far been influenced by ratings so enforcement of the code of conductis often ignored. Ratings also cause uniformity of type of viewing on television stations. Law No. 32 of2002 concerning Broadcasting was born from the spirit of freedom of opinion and obtain the widestpossible information for the community. The Broadcasting Law is a law governing the principles ofbroadcasting that apply in Indonesia. This includes the principles, objectives, functions and directionof national broadcasting, regulating the provisions of the Indonesian Broadcasting Commission,broadcasting services, Public Broadcasting Institutions, Private Broadcasting Institutions, SubscribedBroadcasting Institutions, Community Broadcasting Institutions, Foreign Broadcasting Institutions,Broadcasting Stations and broadcast coverage, and licensing and broadcast activities. The principlesin the Broadcasting Law are held based on the Pancasila and the 1945 Constitution of the Republic ofIndonesia with the principles of benefits, fair and equitable, legal certainty, security, diversity,partnerships, ethics, independence, freedom, and responsibility.